Reticulocytes and Related Parameters in Clinical Practice - Wójcicka, Magdalena; Tomasik, Przemysław (International Journal of Child Health and Nutrition, 2024)
The development of hematologic analyzers allowed us to assess several additional parameters derived in addition to the number of reticulocytes. There is, among others, the calculation of immature reticulocyte fractions, reticulocyte maturity index, reticulocyte production index, and equivalent reticulocyte hemoglobin. The advantage of the equivalent hemoglobin and the content of hemoglobin is the insensitivity to interference by inflammation. These newly introduced parameters expand the possibilities to access bone marrow erythropoietic activity, iron stores, and the effectiveness of iron supplementation, vitamin B12, and folic acid supplementation. These parameters are also used to make decisions about blood transfusions or to detect occult internal bleeding.